The Influence of Different Extraction Methods/Solvents on Composition, Biological Activities and ADMET Predictions of Phenolics in Tribulus terrestris - TAŞKIN, TURGUT (INST TECNOLOGIA PARANA, 2021)
Tribulus terrestris is a plant that has medical importance in treating diseases such as cancer, urinary tract infections, kidney stones, rheumatism, and hypertension. The aim of this study is to examine the effects of extraction methods/solvents on the biological activity and chemical content of the plant and then to determine ADMET predictions of phenolics that were analysed quantitatively using HPLC-DAD in the plant. Maceration methanol (IC50:0.277 mg/mL) and chloroform (0.263 mMFeSO(4)/mg extract) extracts were found to have the strongest DPPH radical scavenging and iron (III) ion reducing activity, respectively. It was determined that Soxhlet methanol (0.0225 mMTE/mg extract) and Soxhlet chloroform (1.360 mMTE/mg extract) extracts exhibited stronger radical cation (ABTS.+) scavenging and cupric ion reducing activity compared to other extracts, respectively. It was found that ultrasonic bath methanol extracts showed the highest anti-urease (21.47%) and calcium oxalate anti-crystallization (71.54%, 80.52%) activity. It was also found that Soxhlet methanol extract (66.763%) has strong acetylcholinesterase enzyme inhibition capacity compared to other extracts. Pyrocatechol, vanillic acid, vanillin, rutin and rosmarinic acid were analysed by HPLC-DAD in the plant. Moreover, it was determined that methanol extracts obtained using soxhlet, ultrasonic bath, and maceration contained the highest amount of rutin, pyrocatechol, and rutin, respectively. ADMET predictions of phenolics show that these compounds are easily absorbed and do not have toxic effects, suggesting that this species may be used as a natural medicinal and nutritional source in the future after detailed analysis tests.
Keywords: antioxidant; enzyme inhibition; anti-crystallization; HPLC-DAD; FREE-RADICALS; ANTIOXIDANT; ACETYLCHOLINESTERASE; CONSTITUENTS; POLYPHENOLS; SAPONINS